INFLUENCE OF BINDING SOLUTION CONCENTRATION, DRYING DURATION AND DRYING TEMPERATURE ON PHYSIOCHEMICAL PERFORMANCE OF NORFLOXACIN GRANULES AND TABLETS - OSMAN, ZUHAEIR; ADAM, NEMAT S.; HASSAN, HASSAN A.; O. NUR, ABUBAKR (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Objective: To investigate the possible individual and joined influences that binding solution concentration, drying temperature and drying duration might have on the physiochemical attributes of granules and tablets using norfloxacin as a model drug. Methods: According to implemented 23 central composite designs, each of the investigated variables were examined at 5 different levels through different 16 formulation runs. For each formulation, obtained granules were qualified for their bulk density, tap density, Hausner ratio, percent of fine and drug content properties whereas the respective tablets were evaluated for their weight variation, drug content, friability, hardness, disintegration, and drug dissolution attributes. Results: Indicated that concentration of binder solution, as compared to drying temperature and drying duration, measured more profound influences on granules' tap density, Hausner ratio, % fine and drug content either through its individual linear and quadratic effects or through its joint effect with drying durations (p<0.05 at 95% CI for all influences). Whilst tablets' friability appeared to be noticeably influenced by the three investigated variables (P ranged 0.001-0.017 at 95% CI), tablets' hardness and disintegration were found to be considerably affected only by binder solution concentration (p = 0.001 and 0.082 at 95% CI, respectively). Moreover, none of the investigated variables has measured a significant influence on tablets' drug content or drug dissolution properties. Conclusion: The study concluded that quadratic and joint influences of variables on attributes of granule and tablet formulations shouldn't be overlooked and better to be considered in the screening design.